Persepsi Pengguna Terhadap Keberadaan Taman Sampangan Sebagai Kebutuhan Rekreasi - Christine Margaretha Batubara; Diah Intan Kusuma Dewi (Department of Urban and Regional Planning, Faculty of Engineering, Diponegoro University, 2018)
Taman Sampangan apply the concept of conformity of functions of RTH as a recreation area where viewed the existing condition of a crowded park visited by the surrounding community. Visitors are doing recreational activities in Taman Sampangan, such as sports, picnics, children's games. However, hard material and soft material elements do not support visitor activity in Taman Sampangan where jogging tracks are used as parking spaces, colloseum and gazebo is not shady, broken children's playground equipment, lack of cleanliness due to difficult-to-reach garbage position, lack of lighting due to damage garden lights and spotlights as well as a lack of interest treatments in the park. Thus, it is necessary to do research with the formulation of the question: